Effect of PFOA exposure on diminished ovarian reserve and its metabolism - Haofei Shen; Min Gao; Qiuyuan Li; Huipeng Sun; Yingdi Jiang; Lihong Liu; Jingyuan Wu; Xiao Yu; Tianyu Jia; Yongan Xin; Shiqiang Han; Yiqing Wang; et al. (BMC, 2023)
Abstract Owing to its difficulty in degrading and ease of accumulation in the body, perfluorooctanoic acid (PFOA) has a detrimental effect on reproduction. This study aimed to examine the effect of PFOA concentration in follicular fluid during ovulation stimulation on embryo quality and the impact of PFOA exposure on the metabolic components of follicular fluid. This was a single-center prospective study that included 25 patients with diminished ovarian reserve (DOR), 25 with normal ovarian reserve (NOR), and 25 with polycystic ovary syndrome (PCOS). Follicular fluid samples were analyzed using ultra-high performance liquid chromatography-tandem mass spectrometry. We demonstrated that the PFOA levels of follicular fluid in the DOR group were higher than those in the NOR group and PCOS group (P < 0.05). PFOA concentration in the PCOS group was negatively correlated with high-quality embryos (P < 0.05). To gain more insight into the impact of PFOA on the metabolic composition of follicular fluid, we classified the DOR group based on the PFOA concentration, for which metabolomic analysis was performed. In the high-concentration PFOA group, there was an increase and a decrease in three and nine metabolites, respectively, compared to that in the low-concentration group. These results suggest that PFOA may alter the metabolic composition of follicular fluid, thus, affecting ovarian reserve function.